First principles investigation of CO and CO2 adsorption on graphene nanoribbon modified by ZrOx - Ahmad I. Ayesh (10188469) (2023)
Carbon dioxide (CO2) is normally emitted from anthropogenic and natural sources, and it is a greenhouse gas that is directly linked to climate change. CO is a main sink of OH molecules in the troposphere to produce CO2. Precise evaluation of the concentrations of the two gases is essential for controlling their emission. The influence of Armchair-graphene nanoribbon (GNR) modification by ZrOx (where x = 0,1,or 2) on its adsorption of CO and CO2 is inspected in this investigation. First principles computations that employ density functional theory (DFT) are utilized to assess gas adsorption by evaluation of the adsorption energy (Ega) and length (D), exchange of charge between the gas and the structure (ΔQT), density of states (DOS), along with the band structure. The modification of GNR is established by atomic substitution (doping) or deposition on GNR structure (decoration). The results indicate outstanding enhancement of CO and CO2 adsorption on the modified GNR structures. However, doping is more efficient than decoration for adsorption of both gases. In particular, the Zr doped GNR has the highest capacity for both gases' adsorption, where the adsorption energy for CO and CO2 increases 18.4 and 16.5 times, respectively, reference to the pristine GNR. The outcomes of this investigation promote the utilization of ZrOx doping of GNR as an approach for the fabrication of highly sensitive and selective environmental CO and CO2 sensors. Other Information Published in: Diamond and Related Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.diamond.2023.110371